2021
DOI: 10.1097/cin.0000000000000741
|View full text |Cite
|
Sign up to set email alerts
|

Academic and Nonacademic Predictors of BSN Student Success on the HESI Exit Exam

Abstract: First-time success rate on the NCLEX-RN examination has significant implications for BSN students, faculty, and schools of nursing. Many nursing programs utilize standardized examinations such as the HESI Exit Exam to quantify student success on knowledge of nursing concepts and to prepare students for success on the NCLEX-RN. Nursing faculty must be able to identify predictors of student success early in the nursing program in order to offer appropriate support and remediation. The purpose of this retrospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…Moreover, investigating the predictive variables of student success on the Exit Exam in a southeastern university, Moore et al (2021) found that higher test anxiety was associated with significantly lower scores. Additionally, higher final grade point averages were significant predictors of students' Exit Exam scores, accounting for 39% of the variance.…”
Section: Variables Affecting Comprehensive Testingmentioning
confidence: 99%
“…Moreover, investigating the predictive variables of student success on the Exit Exam in a southeastern university, Moore et al (2021) found that higher test anxiety was associated with significantly lower scores. Additionally, higher final grade point averages were significant predictors of students' Exit Exam scores, accounting for 39% of the variance.…”
Section: Variables Affecting Comprehensive Testingmentioning
confidence: 99%
“…The retrospective study focused on academic and nonacademic predictors of BSN student success on the HESI exit exam. [10] This study measured students' test anxiety, academic motivation, and academic demographics (age, SAT/ACT scores, final GPA, and scores on other HESI exams). A total of 486 student records were reviewed.…”
Section: Introductionmentioning
confidence: 99%